Analysis of clothing pressure based on material of virtually-fitted swimsuits and wearer body type and movement using 3D fashion design software - Jisoo Kim; Youngjoo Chae (PLoS ONE, 2025)
This study aimed to evaluate and compare the clothing pressure of adult women’s full-body swimsuits based on body type, swimming posture, and fabric material. By using the CLO 3D virtual fitting system, we conducted both qualitative and quantitative analyses to assess pressure distribution across four major body regions during five swim-related movements. Five female body types—hourglass, apple, rectangle, triangle, and inverted triangle—and five movements—overhead arm raise, forward bend, T-pose, flutter kick, and cobra pose—were analyzed. The swimsuits used two fabric types—nylon 80% + spandex 20% blend fabric and polyester 80% + spandex 20% blend fabric; garment pressur e was measured at the chest, back, waist, and abdomen. The findings showed that CLO 3D had limitations in precisely distinguishing the characteristics of nylon and polyester, specifically in terms of clothing pressure and overall comfort. Significant variations in clothing pressure across different body parts were observed depending on swimming movement and body type. According to body type, the highest pressure was on the abdomen for the apple shape and the chest for inverted triangle shape. Regarding movement, the highest pressure was on the abdomen during the forward bend and chest during the cobra pose, indicating possible discomfort in those areas. Moreover, while the CLO 3D system effectively analyzes garment pressure in relatively static conditions of the wearer, it has limitations in assessing underwater environments and wearers’ dynamic states. This study recommends configuring the underwater environment, establishing a database of swimsuit fabric properties in a wet state, incorporating movements, and automatic correction of discrepancies between measured compressive force data and CLO 3D output. The findings provide a data-driven design direction to enhance wearability and functionality in swimsuit development, while presenting new possibilities for CLO 3D-based sportswear research without the need to use traditional human-wear trials.